APLIKASI TRANSAKSI PENJUALAN BERBASIS WEB PADA ROMBONG AKSESORIS - Andi Martasya; Farida Idifitriani (Universitas Teknologi Sumbawa, 2023)
Rombong Accessories Sumbawa is one of the trading business businesses engaged in mobile phone accessories and electronic goods. The background of this research is the Rombong Accessories sales transaction data management system which still uses manual methods, so that the management and updating of data and reports are not managed properly and even human error often occurs. The purpose of this study is to assist Rombong Accessories Sumbawa in managing sales transaction data and reducing existing problems. The result of this research is a Web-based sales transaction application built using the Rapid Application Diagram system development method, Unified Modelling Language (UML) modeling and PHP programming language with Laravel framework and MYSQL database and has been tested using the Black Box Testing method.